Shape memory alloys phenomena: classification of the shape memory alloys production techniques and application fields - Ozkul, Iskender; Kurgun, Mehmet Ali; Kalay, Ece; Canbay, Canan Aksu; Aldas, Kemal (Springer Heidelberg, 2019)
The shape memory alloy, referred to as the material of the future, is the first to come to mind in the class of smart materials. Shape memory alloys are already present in many important areas. In the medical field, glasses frame material, the material of intravenous stents, jet engines in the aviation area, and bridges in the construction area can be mentioned. Although the shape memory effect is found in different material types such as ceramics and polymer, shape memory alloys are the most commonly used among these materials. The atomic-bond types of the alloys provide long-lasting and durable properties compared to other material types. The extraordinary mechanics of solid-state transformation and the kinematics of the bonds between atoms exhibit a unique nature formation. Discovered too late in the history of humanity, this feature changed the material understanding of the last 80 years and enabled industrial application to have a very important function coming from intelligent material types. In this study, a detailed study on the mechanical characterization of shape memory alloys in microstructure, types of shape memory effect, shape memory alloy, phase transformations and applications are presented.
Keywords: Martensitic-Transformation; Phase-Transformation; Mechanical-Properties; Behavior; Temperature; Microstructure; Stabilization; Recovery; Systems; Stress